Participation of ezrin in bacterial uptake by trophoblast giant cells - Kim Suk; Tachibana Masato; Watanabe Kenta; Watarai Masahisa (BMC, 2009)
Abstract Background Trophoblast giant (TG) cells are involved in systematic removal of bacterial pathogens from the maternal-fetal interface of the placenta. In particular, TG cells have the ability to take up extracellular antigens by active phagocytosis induced by interferon-gamma (IFN-gamma). We previously reported that heat shock cognate protein 70 (Hsc70) present on the surface of TG cells mediated the uptake of Brucella abortus. However, the mechanism of bacterial uptake by TG cells is not completely understood. Here we identified ezrin, a member of ezrin-radixin-moesin (ERM) protein family, as a molecule associated with Hsc70. Methods Mouse TG cells were employed in all experiments, and B. abortus was used as the bacterial antigen. Confirmation of the binding capacity of ERM protein was assessed by pull-down assay and ELISA using recombinant Hsc70 and ERM proteins. Ezrin was depleted using siRNA and the depletion examined by immunoblotting or immunofluorescence staining. Results The expression level of ezrin was higher in TG cells than in trophoblast stem (TS) cells, and ezrin knockdown TG cells showed a reduction in bacterial uptake ability. Although tyrosine phosphorylation of ezrin was not related to bacterial uptake activity, localization of Hsc70 on the membrane was affected by the depletion of ezrin in TG cells. Conclusion Ezrin associates with Hsc70 that locates on the membrane of TG cells and participates in the bacterial uptake by TG cells.